Access time based on initial head position in disk scheduling - Janwa, Mr. Naresh; Pal, Mr. B.L (IJRDO -Journal of Computer Science Engineering, 2015)
As we know that most of the job in computeris performed on the basis of job scheduling algorithm by disk access. The basic parameter of all thesealgorithm is head movement. The criteria for best algorithm is minimum head movement to perform thesame job, whether algorithm used to perform job is LOOK or C-LOOK or C-SCAN or SCAN or SSTF orFIFO. Most jobs in computer depend heavily on disk access. But now, question arises “How to improve diskaccess time?” This can be done by scheduling the request for disk access for operating system. If thedesired disk drive and controller are available the access can be immediately. in any system when the driveis operating, the disk is rotates at constant speed. To read or write, the head must be positioned at thedesired track and at the beginning of the desired sector on that track. Track selection involves moving the headin a movable-head system. The performance of disk schedulers is affectedby many factors such as initial head position, workloads, file systems, and disk systems. Diskscheduling performance can be improved by positioning the Read/Write Heads at appropriate position.Scheduler performance tuning is mostly done manually. To automate this process, we propose initial headposition in disk scheduling schemes. We conducted experiments to compare the performance and overheadof algorithms. In this paper, we are going to study or analyzeFIFO, SSTF or SCAN algorithm on the basis of increasing the range of head position from 0 - 200 to 0 -500 because all these algorithms are analyzed previously on the basis of range from 0- to 200 whetherit is done by using IBM’s disk or HP disk.